Suppression of Skyrmion Hall Motion in Antiferromagnets Driven by Circularly Polarized Spin Waves - Guan, S. H.; Yang, Y.; Jin, Z.; Liu, T. T.; Liu, Y.; Qin, M. H. (Frontiers in Physics, 2021)
An investigation of spin waves interacting with antiferromagnetic spin textures is meaningful for future spintronic and magnonic-based memory and logic applications. In this work, we study numerically the skyrmion dynamics driven by circularly polarized spin waves in antiferromagnets and propose a method of suppressing the Hall motion. It is demonstrated that the application of two circularly polarized spin waves with opposite chirality allows the skyrmion motion straightly along the intersection line of the two spin wave sources. The skyrmion speed depending on these parameters of the spin waves and system is estimated, and a comparison with other methods is provided. Furthermore, two depinning behaviors of the skyrmion related to the strengths of the defect are also observed in the simulations. Thus, the proposed method could be used in precisely modulating the skyrmion dynamics, contributing to skyrmion-based memory device design.